PERANCANGAN PROGRAM APLIKASI SISTEM BASIS DATA KUESIONER PENELITIAN BERBASIS WEB - Dodi Putra; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
In today's modern era computers were instrumental to the advancement of an organization, which for the process is done by using a computer can be very helpful in shortening the time. At one of them is on the IS and STS lab, where there are researchers who are in the lab. They do research and process and store data, processing and storage of data is done is still done by hand, they get the data to be processed by distributing questionnaires, after getting past the data they process and store, processing and storage is still manual is by using micrfosoft excel therefore need to be made designing a database system application program questionnaire web-based research to assist in processing and storing as well as generate a report questionnaire with time quickly and accurately.Key wordsdatabase, research, questionnaries